2021
DOI: 10.1186/s12883-021-02262-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic and post-epidemic periods on the process of endovascular treatment for acute anterior circulation ischaemic stroke

Abstract: Background and purpose The purpose of our study was to analyse endovascular treatment (EVT) in patients presenting acute anterior circulation ischemic stroke with large-vessel occlusion (AIS-LVO) during the pandemic and post-epidemic periods. Methods Patients with AIS-LVO of the anterior circulation who underwent EVT were enrolled. According to the times of Wuhan closure and reopening, patients were divided into a pre-pandemic group (from November … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The included articles were composed of 46 retrospective studies (cohort (n=7); observational (n=11); cross-sectional (n=3); archive (n=1); review (n=1); unspecified (n=23)); 10 prospective studies (cohort (n=2); observational (n=3); cross-sectional (n=3); unspecified (n=2)); 26 observational studies (reports (n=9); cohort (n=7); cross-sectional (n=1); unspecified (n=9)); one matched pairs study; and one survey and one exploratory design. The included articles demonstrated wide geographical spread spanning Bangladesh 29 ; Canada 3032; Chile 33 ; China 15,3437,3744; Egypt 45 ; Finland 46 ; France 47 ; Germany 4850; India 51 ; Iran 52,53 ; Israel 5456; Italy 8,5767; Japan 9,68 ; Lithuania 69 ; Malaysia 70 ; Netherlands 71 ; Norway 72,73 ; Saudi Arabia 74,75 ; Spain 7679; Switzerland 80 ; Taiwan 81 ; United Kingdom 8284; and United States of America 7,20,24,39,85104 . The studies encompassed participants from a wide range of diverse backgrounds, including individuals from various racial and ethnic communities, linguistic minorities, and persons with differing levels of disability.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The included articles were composed of 46 retrospective studies (cohort (n=7); observational (n=11); cross-sectional (n=3); archive (n=1); review (n=1); unspecified (n=23)); 10 prospective studies (cohort (n=2); observational (n=3); cross-sectional (n=3); unspecified (n=2)); 26 observational studies (reports (n=9); cohort (n=7); cross-sectional (n=1); unspecified (n=9)); one matched pairs study; and one survey and one exploratory design. The included articles demonstrated wide geographical spread spanning Bangladesh 29 ; Canada 3032; Chile 33 ; China 15,3437,3744; Egypt 45 ; Finland 46 ; France 47 ; Germany 4850; India 51 ; Iran 52,53 ; Israel 5456; Italy 8,5767; Japan 9,68 ; Lithuania 69 ; Malaysia 70 ; Netherlands 71 ; Norway 72,73 ; Saudi Arabia 74,75 ; Spain 7679; Switzerland 80 ; Taiwan 81 ; United Kingdom 8284; and United States of America 7,20,24,39,85104 . The studies encompassed participants from a wide range of diverse backgrounds, including individuals from various racial and ethnic communities, linguistic minorities, and persons with differing levels of disability.…”
Section: Resultsmentioning
confidence: 99%
“…Many articles discussed the impact of the COVID-19 pandemic on hospital admissions for stroke patients 9,15,29,36,40,44,45,[47][48][49][50][51][52][53][54]58,60,61,65,66,69,71,72,82,83,86,88,91,103,104 . A few articles mentioned a decrease in the number of stroke admissions during the pandemic 29,39,40,52,53,69,72,76,77,79,83,84,90,97,107 despite reperfusion therapy, thrombolysis and thrombectomy rates remaining unchanged during this period 50,54,63,65,…”
Section: Domain Summary 7: Reduction In Stroke Admissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the first case of COVID-19 was reported in Wuhan, China in December 2019 (2), more than 762 million confirmed cases and 6.8 million deaths worldwide have been reported by the World Health Organization (WHO) as of April 8, 2023 (3). China adopted proactive control policies in June 2020 to fight COVID-19 and has entered the post-pandemic era (4,5) with the majority of the population vaccinated (6) and a lower fatality rate than before (7). Studies in various countries (8)(9)(10) revealed that people's psychological stress under COVID-19 directly affected their quality of life and work performance.…”
Section: Introductionmentioning
confidence: 99%